Multi-Disciplinary Approach in Indonesian Islamic Higher Education: A Western Perspective upon Epistemological Problem, Challenge, and Critique - Auliya Ridwan (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
The development of several Institute of Islamic Studies into Islamic Universities brings consequences to living religious disciplines vis-à-vis secular disciplines. A multi-disciplinary approach is adopted by positioning al-Quran and Hadits as the foundation of scientific development. This paper attempts to bring western perspective in examining epistemological issues in Indonesian Islamic higher education’s multi-disciplinary approach, its challenges, and critiques. Religious discipline’s domain cannot fully be examined from secular discipline’s framework, as it will result in contra-productive confrontation between the two authorities. Therefore, the challenge for this approach is defining which are autonomous areas in the two domains and which is the intersection. Pragmatically, this approach must result in new genres, which are more productive for the development of mankind civilization.